Development and Preliminary Evaluation of a Positive Emotion Regulation Augmentation Module for Anxiety and Depression. Issue 6 (November 2018) - Carl, Jenna R.; Gallagher, Matthew W.; Barlow, David H.
Abstract: Research has shown that positive emotions are important to optimal health, functioning, and well-being, and contribute to resilience against psychological dysfunction. Many clinical disorders, particularly anxiety and mood disorders, are associated with deficits in positive emotion that may contribute to disorder severity and prevent full recovery, and these deficits have received insufficient attention in treatment. The present study represents a preliminary evaluation of the feasibility and utility of adding a novel brief intervention module for enhancing positive emotion in anxiety and depressive disorders to existing evidence-based treatment. This intervention was evaluated in nine patients with a range of principal anxiety disorders who had previously completed an initial course of cognitive-behavioral treatment, utilizing a multiple baseline experimental-across-participants design. Results indicated that the intervention was effective in improving positive emotion regulation skills for five of nine participants. The intervention was also associated with further improvements in anxiety and depressive symptoms, positive and negative emotion, functioning, quality of life, and well-being. Participants reported high acceptability and satisfaction with the study intervention. Future research is needed to confirm the validity of these findings and evaluate the generalizability of these effects across patients and settings. Highlights: Anxiety and depression are associated with difficulties regulating positive emotion. A novel CBT augmentation module for addressing these difficulties is proposed. The module improved positive emotion regulation in five of nine cases. The module received high ratings of acceptability and satisfaction.